Pengaruh Informasi Asimetris terhadap Penciptaan Senjangan Anggaran dengan Faktor-faktor Person-Situation Interactionist sebagai Variabel Pemoderasi (Studi pada Organisasi Perangkat Daerah Kabupaten Banyumas) - Marliandi Tri Baryatdika; Mafudi Mafudi; Triani Arofah (Ekonomi dan Bisnis, 2019)
This research is an explanatory and correlational study using survey method on heads of division in Regional Organizations of Banyumas Regency. This research aims to find out the effect of asymmetric information on the creation of budgetary slack and the effect of ethical factors expressed by person-situation interactionist factors on that relationship. The research population are all Regional Organizations of Banyumas Regency. The sampling method used is judgment sampling and it obtains 25 regional organizations. There are 4 heads of divisions from each regional organization who become the respondents.Based on the research result and data analysis using moderated regression analysis, it concludes: Asymmetric information can increase the creation of budgetary slack; (2) Ethical ideology does not moderate the effect of asymmetric information on the creation of budgetary slack; (3) Machiavellian character does not moderate the effect of asymmetric information on the creation of budgetary slack; (4) Locus of control does not moderate the effect of asymmetric information on the creation of budgetary slack; (5) Moral intensity does not moderate the effect of asymmetric information on the creation of budgetary slack; and (6) Organizational ethical climate does not moderate the effect of asymmetric information on the creation of budgetary slack.